Diseño de un plan de marketing para la empresa Textiltelinsco Cia Ltda. Ubicada en el cantón Rumiñahui provincia de pichincha. - Quezada Tipantuña, Yadira (2014)
The Textiltelinsco Company is located in the Valle de los Chillos in the city of Sangolquí Pichincha Province, the same dedicated to the purchase and sale of textile inputs and supplier of small businesses whose sales are based on a craft level sport uniforms. This company was raised to make a marketing plan and thus consolidated in the domestic market as one of the most important companies in the textile market. With a solid marketing plan based on the market and the reality of the country, the company developed new techniques Textiltelinsco Information and thus come to occupy a place run a business excellence. Currently the company has Textiltelinsco negative numbers in their economic and financial information, which after making a study and evaluated each area of the company has proposed to make a marketing plan to help the company reorganize and implement your environment work on corporate image and strategies to increase sales as its main shortcoming.